Entrepreneurship Education as A Catalyst for Self-Employment and Economic Growth in Karachi - Imran Azeem; Waheed Akbar Khaskheli; Nisar Ahmed Solangi (Social Science Review Archives, 2025)
Entrepreneurship education has emerged as a transformative strategy for fostering self-employment and driving economic growth in urban economies. Karachi, the economic hub of Pakistan, faces significant unemployment challenges, particularly among youth and women, exacerbating socioeconomic disparities. This paper explores the pivotal role of entrepreneurship education as a catalyst for self-employment and economic growth in Karachi. The study delves into the multifaceted components of entrepreneurship education, including business knowledge dissemination, skill development, innovation cultivation, financial literacy, and mentorship. It evaluates the effectiveness of various public and private sector programs in equipping individuals with entrepreneurial capabilities, thereby enhancing self-reliance and contributing to job creation. The findings suggest that comprehensive entrepreneurship education programs can significantly improve self-employment rates, stimulate innovation, and promote inclusive economic growth. The paper concludes with policy recommendations aimed at optimizing entrepreneurship education as a strategic tool for sustainable socioeconomic development in Karachi.